1992
DOI: 10.2151/jmsj1965.70.1b_319
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Heating of the Tibetan Plateau and Its Effects on the Evolution of the Asian Summer Monsoon

Abstract: Using the objectively analyzed FGGE II-b upper-air data, the large-scale circulation, heat sources and moisture sinks over the Tibetan Plateau and surrounding areas are examined for a 9-month period from December 1978 to August 1979. In addition to the FGGE data, special soundings obtained during the Chinese Qinghai-Xizang (Tibet) Plateau Meteorological Experiment (QXPMEX) from May to August 1979 are also used in the objective analyses.The evolution of the large-scale flow patterns, temperature, outgoing longw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

22
586
0
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 860 publications
(642 citation statements)
references
References 101 publications
22
586
0
2
Order By: Relevance
“…Rather the monsoon begins abruptly in a period as short as two weeks, as measured not only by precipitation [e.g., Soman, 1988, 1989;Joseph et al, 2006;Pai and Nair, 2009;Soman and Krishna Kumar, 1993], but also by reversals in both low-level winds [e.g., Boos and Emanuel, 2009;Fieux and Stommel, 1977;Halpern and Woiceshyn, 1999;Krishnamurti et al, 1981] and upper troposphere circulation [e.g., He et al, 1987He et al, , 2003Li and Yanai, 1996;Wu and Zhang, 1998;Yanai and Wu, 2006;Yanai et al, 1992]. Moreover, Goswami et al [1999] showed that the reversal in winds aloft correlates with onsets of monsoons defined by various rainfall indices.…”
Section: Introductionmentioning
confidence: 99%
“…Rather the monsoon begins abruptly in a period as short as two weeks, as measured not only by precipitation [e.g., Soman, 1988, 1989;Joseph et al, 2006;Pai and Nair, 2009;Soman and Krishna Kumar, 1993], but also by reversals in both low-level winds [e.g., Boos and Emanuel, 2009;Fieux and Stommel, 1977;Halpern and Woiceshyn, 1999;Krishnamurti et al, 1981] and upper troposphere circulation [e.g., He et al, 1987He et al, , 2003Li and Yanai, 1996;Wu and Zhang, 1998;Yanai and Wu, 2006;Yanai et al, 1992]. Moreover, Goswami et al [1999] showed that the reversal in winds aloft correlates with onsets of monsoons defined by various rainfall indices.…”
Section: Introductionmentioning
confidence: 99%
“…[4] The Tibetan Plateau (TP), with an average elevation of over 4000 m above sea level (asl), is the highest and largest highland in the world and exerts a great influence on regional and global climate through its thermal forcing mechanisms [Duan and Wu, 2005;Yanai et al, 1992;Yeh and Gao, 1979]. Previous studies [Duan and Wu, 2006;Kang et al, 2007;Lin and Zhao, 1996; X.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have suggested that the seasonal variability of the Tibetan heating and the consequent anomalies of temperature may trigger a change of large-scale atmospheric circulation, leading to the seasonal variations of the monsoons and associated rainfall over South Asia and East Asia (Yanai et al, 1992;Li and Yanai, 1996;Webster et al, 1998;Zhao and Chen, 2001a, b;He et al, 2008). Wu et al (2002) emphasized an important role of Tibetan heating on the evolution of atmospheric circulation.…”
Section: Introductionmentioning
confidence: 99%